Indonesian Journal of Obstetric and Gynecology=Majalah Obstetri dan Ginekologi Indonesia, Vol.3 No.2 Halaman 65-120, April 2015 - Perkumpulan Obstetri Dan Ginekologi Indonesia (POGI, 2015)
-Different of Vertical Transmission in HIV-Infected Women with Complete and Incomplete PMTCT -Placental Growth Factor Level in Preeclampsia Compared to Normal Pregnancy -User Profile and Factors Correlating to Duration of Intrauterine Device Use -Modification of Immediate Postplacenta CuT-380A IUD Intertion Using Ring Forceps and Standart Inserter: Twelve Months Follow Up -Factors Affecting Selection of Contraceptive Methods and Its Legth of Use -Prevelence of Lower Urinary Tract Symptoms in Women Based on Bahasa Indonesia Validated ICIQ-FLUTS Long Form -Clinical Evaluation of Neoadjuvant Chemotherapy Followed by Radical Hysterectomy in the Management of Cervical Cancer Stage IIB -Survival and Side Effects of Cisplatin/Cyclophosphamide and Carboplatin/Paclitaxel Adjuvant Chemotherapy in Stage IC_IV Ovariuan Cancer -A Real-Time Optoelectronic Device in Screening of Precancerous Cervical Lesion